2019
DOI: 10.1371/journal.pone.0215726
|View full text |Cite
|
Sign up to set email alerts
|

Negative affectivity and social inhibition are associated with increased cardiac readmission in patients with heart failure: A preliminary observation study

Abstract: Background Type D personality was hypothesized to influence clinical and patient-centered outcomes patients with heart failure. The aim of this study was to investigate the association between negative affectivity and social inhibition components of Type D personality and cardiac readmission in patients with heart failure. Methods A prospective observational study design was used. A total of 222 patients with heart failure were recruited from the department of cardiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…Some studies found that coronary heart disease patients with Type D personality reported a relatively poorer quality of life compared with those who did not have a Type D personality (Ginting et al., 2016; Widdershoven et al., 2013). Moreover, having the Type D personality was associated with adverse clinical outcomes, including hospital readmission and mortality in patients with heart failure (Bundgaard et al., 2019; Lin et al., 2019; Staniute et al., 2015). This personality type has also been reported to affect self‐care behaviours (Cao et al., 2016; Ginting et al., 2016; Widdershoven et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that coronary heart disease patients with Type D personality reported a relatively poorer quality of life compared with those who did not have a Type D personality (Ginting et al., 2016; Widdershoven et al., 2013). Moreover, having the Type D personality was associated with adverse clinical outcomes, including hospital readmission and mortality in patients with heart failure (Bundgaard et al., 2019; Lin et al., 2019; Staniute et al., 2015). This personality type has also been reported to affect self‐care behaviours (Cao et al., 2016; Ginting et al., 2016; Widdershoven et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Data. Lin et al (2019) performed an observational study aimed at unravelling patient-level characteristics associated with hospital readmission after earlier heart failure hospitalization. They focused on the distressed personality construct (Type D personality) which is a joint disposition towards negative affectivity and social inhibition.…”
Section: Illustrative Examplementioning
confidence: 99%
“…В последующих исследованиях на отдельных когортах пациентов получены также противоречивые результаты. Так, у больных стабильной ИБС при проспективном наблюдении не менее 1 года тип Д был ассоциирован с худшим прогнозом [35], при выполнении кардиохирургических операций наличие типа Д ассоциировано с более длительными периодами мозговой дисфункции (делирий/кома) [36], у больных после коронарного шунтирования -с более частым развитием сердечно-сосудистых событий в отдаленном периоде [37], у больных ХСН -с частотой повторных госпитализаций [38]. В то же время при неишемической ХСН не удалось выявить неблагоприятного прогностического влияния типа личности Д в исследовании DANISH [39], также не влиял тип личности Д на прогноз у больных после имплантации кардиовертера-дефибриллятора [40], а также в течение года после имплантации коронарных стентов [41].…”
Section: тип д: место среди других психосоциальных факторов рискаunclassified